Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Multimedia Virtual Lab PhEt Terhadap Hasil Belajar Kimia Materi Asam Basa - Aqza, Bella Hasbi; Haris, Mukhtar; Supriadi (Chemistry Education Practice, 2024)
The purpose of this study is to determine how the utilization of PhET multimedia virtual laboratory in interactive teaching materials impacts the acquisition of acid-base chemistry knowledge among grade XI students. This research was conducted through a pre-experimental design consisting of pre-test and post-test one group measurements. All students of class XI MIPA SMAN 1 Alas Sumbawa Besar constituted the population, while purposive sampling was conducted on class XI MIPA 3 consisting of 34 four students. Data collection instruments such as questions during the pre-test and post-test as well as survey sheets were valid and reliable for the purpose of data assessment. Both multiple choice questions and description questions have a high level of reliability, with values of 0.65 and 0.63 respectively. In addition, the average value of the Aiken V index for validity was found to be at the valid category level of 0.66. The questionnaire instrument used has a high level of reliability and validity with a value of 0.77 and high validity with the average value of the Aiken V index which is in the very valid category range with a value of 0.84. Data analysis techniques such as the N-gain test, normality test, and t-test were used to measure student learning outcomes, while reactions were assessed using the student interest test and resulted in an overall average N-gain value equivalent to a higher value scale. The pre-test significance (sig) value of 0.621 > 0.05 and the post-test value of 0.063 > 0.05 indicated that the pre-test and post-test data values were normally distributed, in accordance with the normality test results. The t-test resulted in a significance level of 0.000 < 0.05 (2-tailed). On the other hand, 74% of students' responses to the use of the materials fell into the interested group. The research findings show that the interest and learning outcomes of chemistry class XI IPA students of SMAN 1 Alas Sumbawa Besar are positively influenced by interactive learning materials based on virtual multimedia PhET lab on acid-base materials.